Differences in aggressive behavior of male and female students using Rasch stacking - Alizamar Alizamar; Yuda Syahputra; Afdal Afdal; Zadrian Ardi; Leviana Trizeta (Universitas Negeri Padang, 2019)
Aggressive behavior that occurs among students nowadays indicates a decrease in the quality of education. One of the things that cause this is education which only emphasizes cognitive quality without being balanced with affective. This study aims to describe the differences in aggressive behavior between male and female students in Junior High School of West Sumatera. The sample consisted of 360 students (159 male and 201 female) spread across eight Junior High Schools in West Sumatera. The analysis technique used is the independent sample t-test combined with stacking RASCH model. The analysis show that in general there are differences in aggressive behavior between male and female students. The discussion regarding guidance and counseling services was further explained.